THE CONVERGENT VALIDITY OF INDONESIAN VERSION OF PID-5 - Adhiatma, Widhi; Hendrianti, Josephine (Jurnal Psikologi, 2018)
Personality Inventory for DSM-5 (PID-5) is the latest personality inventory that measures pathological personality based on DSM-5 model. As a clinical instrument, validity testing is an essential procedure to be achieved, so the clinicians could ascertain the accuracy of the test results. This study aims to measure the convergent validity of Indonesian Version of PID-5. The relationship between PID-5 domains and Personality Psychopathology Five-revised (PSY-5-r) subscales from Minnesota Multiphasic Personality Inventory-2 Restructured Form (MMPI-2-RF) was being measured in this study. All participants were university students (n = 72, M = 22.24 years old, SD = 6.00, males 45.8% and females 54.2%). The PID-5 and MMPI-2-RF which have been adapted into Bahasa Indonesia was administered to all participants. Pearson correlation was used to measure the relationship between each domain from PID-5 (i.e. Negative Affectivity, Antagonism, Detachment, Disinhibition, and Psychoticism) with PSY-5-r subscales (i.e. Negative Emotionality, Aggressiveness, Introversion, Disconstraint, and Psychoticism). Most of the PID-5 domain showed the highest correlation with its conceptually expected PSY-5-r counterpart (r = .31 - .75; Mdnr = .54; p < .01, two tails), except for Disinhibition domain, which showed higher correlation with Negative Emotionality (r = .59) than Disconstraint (r = .31). This slight variation of correlation pattern notwithstanding, the overall result still suffices to confirm a pattern of convergence betwÂeen PID-5 domains and PSY-5-r subscales.